STRATEGI KOMUNIKASI LINGKUNGAN PECINTA ALAM BAHARI (PAB) DALAM MELESTARIKAN HUTAN MANGROVE KOTA DUMAI - Nurazira, Tengku; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Pecinta Alam Bahari do the preservation of mangrove forests because mangrove forests are forest formations that grow and develop on gentle slopes in river estuaries and coastal areas that are affected by tides, and can withstand high waves of surface such as tsunami. In addition, PAB is carrying out a preservation of mangrove forests and mangrove forests in the city of Dumai due to the existence of a cultural value in the area. Not only that, PAB is carrying out the preservation of mangrove forests due to the near extinction of mangrove species in Riau, thus making PAB take the initiative to defend the land and also preserve mangrove forests. Therefore, this study aims to determine the environmental communication strategies of PAB and barriers received by PAB in the process of preserving mangrove forests. The method used in the research descriptive qualitative. The research selected 3 key informan that is, Mr. Darwis Moh. Saleh, Mrs. Fatmawati and Mr. Effendi, 2 supporting informants as a source of information that is Reza and Said as the local community. To collect data, the research used interview, observation and documentation study. Be descriptive presentation to answer questions that have been identified previously. Results of this study indicate that the Pecinta Alam Bahari (PAB) always implement the preservation of mangrove forests for the selves and the society. Preservation of mangrove forests can be seen from good development mangrove forests region named Bandar Bakau. Not only that, the mangrove forests area becomes ecotourism in Dumai City, with the intervention of Pecinta Alam Bahari (PAB) by bring peoples to participate in preserving mangrove forest, and that mangrove forest region becomes very good and comfortable for visitor to relax until now.Keyword : Communication Environment, Communication Strategy, Mangrove Forest